Metabolic Acidosis Suppresses 25-Hydroxyvitamin D(3)-1α-Hydroxylase in the Rat Kidney: DISTINCT SITE AND MECHANISM OF ACTION - Kawashima, Hiroyuki (1982)
Effect of metabolic acidosis on two distinct 25-hydroxyvitamin D(3)-1α-hydroxylase (1α-hydroxylase) systems was studied in the kidneys of vitamin D-deficient rats; one is localized in the proximal convoluted tubule (PCT), is activated in vitamin D deficiency, and is regulated primarily by parathyroid hormone (PTH) via cyclic AMP; the other is localized in the proximal straight tubule (PST), is latent in vitamin D deficiency, and is selectively stimulated by calcitonin via a cyclic AMP-independent mechanism. The 1α-hydroxylase activities were measured in the PCT and PST microdissected from the kidney of vitamin D-deficient rats with or without metabolic acidosis of varying duration. The 1α-hydroxylase activity decreased in the PCT from 0.74±0.07 fmol/mm per h to 0.24±0.02 at day 3 of metabolic acidosis without a further decline at day 7. Neither metabolic acidosis of 16 h duration nor reduction of the incubation medium pH from 7.4 to 7.0 affected the enzyme activity in the PCT. To examine the underlying mechanism for the suppression of 1α-hydroxylase activity, PTH, cyclic AMP, or calcitonin was given to rats with metabolic acidosis of 3 d duration. Although PTH failed to augment the suppressed 1α-hydroxylase activity in the PCT, cyclic AMP restored it to the level of control rats. The 1α-hydroxylase activity in the PST remained undetectable in control rats and in acidotic rats with or without PTH or cyclic AMP treatments. However, calcitonin stimulated the 1α-hydroxylase activity in the PST equally from undetectable to 0.75±0.09 fmol/mm per h in control and to 0.78±0.10 in acidotic rats. The data suggests that metabolic acidosis suppresses 1α-hydroxylase only in the PCT by inhibiting PTH-dependent adenylate cyclase, and that cellular events beyond cyclic AMP in the PCT and the events responsive to calcitonin in the PST are unaffected. The results show the definite advantage of using defined single nephron segments to study the hormonal and ionic control of the 1α-hydroxylase system in the kidney.